A nomenclatural and taxonomic review of the names and new combination published between 1886 and 1931 in Kalanchoe (Crassulaceae subfam. Kalanchooideae) by British botanist Nicholas Edward Brown (1849–1934) - Smith, Gideon F. (Phytotaxa, 2023)
The British botanist Nicholas Edward Brown (1849–1934) who worked in the Herbarium of the Royal Botanic Gardens, Kew, from 1873 until well beyond his retirement, had a special interest in succulent plants, predominantly, but not exclusively, the Aizoaceae, the vygie family. He also described 12 species of Kalanchoe (Crassulaceae subfam. Kalanchooideae) as new, and published one new combination in the genus for a species that he had earlier placed in Cotyledon. The nomenclature and taxonomy of the names published in Kalanchoe by Brown is reviewed and discussed in a historical context. Where necessary, the names are typified.